Investigation of Firn Aquifer Structure in Southeastern Greenland Using Active Source Seismology - Montgomery, Lynn N.; Schmerr, Nicholas; Burdick, Scott; Forster, Richard R.; Koenig, Lora; Legchenko, Anatoly; Ligtenberg, Stefan; Miège, Clément; Miller, Olivia L.; Solomon, D. Kip (Frontiers in Earth Science, 2017)
In spring of 2011, a perennial storage of water was observed in the firn of the southeastern Greenland ice sheet, a region of both high snow accumulation and high melt. This aquifer is created through percolation of surface meltwater downward through the firn, saturating the pore space above the ice-firn transition. The aquifer may play a significant role in sea level rise through storage or draining freshwater into the ocean. We carried out a series of active source seismic experiments using continuously refracted P-waves and inverted the first P-arrivals using a transdimensional Bayesian approach where the depth, velocity, and number of layers are allowed to vary to identify the seismic velocities associated with the base of the aquifer. When our seismic approach is combined with a radar sounding of the water table situated at the top of the firn aquifer, we are able to quantify the volume of water present. In our study region, the base of the aquifer lies on average 27.7±2.9 m beneath the surface, with an average thickness of 11.5±5.5 m. Using a Wyllie average for porosity, we found the aquifer has an average water content of 16±8%, with considerable variation in water storage capacity along the studied east-west flow line, 40 km upstream of the Helheim glacier terminus. Between 2015 and 2016, we observed a 1-2 km uphill expansion of the aquifer system, with a site dry in summer 2015 exhibiting a water content of 530 kg m-2 in summer 2016. We estimate the volume of water stored in the aquifer across the entire region upstream of Helheim glacier to be 4.7±3.1 Gt, approximately 3% of the total water stored in firn aquifers across the Greenland ice sheet. Elucidating the volume of water stored within these recently discovered aquifers is vital for determining the hydrological structure and stability of the southeastern Greenland ice sheet.